Kualitas Penyelenggaraan Pelayanan Kartu Tanda Penduduk (KTP) Elektronik Melalui Unit Pelaksana Teknis (Upt) Dispendukcapil Kecamatan Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Pasuruan - Subihandoko, Randika Didik (FIA UB, 2017)
Lecturers as professional workers are required to improve their productivity through four aspects, they are: (1) implement leadership and teaching, (2) conduct research, (3) carry out community service and (4) lecturersâ activities support. Empowerment implies that the potential within every lecturer can be used optimally. This research is conducted with 107 lecturers in University of Brawijaya. Data is analyzed through path analysis to prove the correlation between the leadership with the productivity of lecturers mediated by empowering of lecturer. The results of this research is the leadership and empowerment significantly effect the productivity of lecturers. Lecturersâ empowerment proven able to mediate between leadership with lecturersâ productivity.Â The Quality of Implementation of Identity Card Service (KTP-el) in Pasuruan Regency generally assess the performance of the service is still not as expected, this can be seen among others from the many complaints or complaints from the public either through Mass Media or electronic media, also through Media Social such as facebook, whats app and so forth including through website Dispendukcapil Complaint Pasuruan regency as related to procedure and mechanism of service which less, not transparent, less informative, less accommodative, limited facilities, facilities and infrastructure services, the bureaucratic structure that is perceived Entangled in procedures in the issuance of Electronic Identity Card (KTP) which takes a long time and there is no certainty when it happens, so a lot of electronic Card Identity Card (KTP) file that has not been completed or has not been months, server with application system Which is often problematic, lack of socialization so as not to guarantee the certainty of time and there are still many illegal levies (pungli) and actions that are indicative of irregularities and corruption (KKN). The Quality of Electronic Identity Card (KTP) Service at the Population and Civil Registry Office of Pasuruan Regency which currently has Technical Implementation Unit (UPT) Dispendukcapil in the sub-district is still not known clearly the existence, because it can not provide maximum service in accordance with Community expectations, such as the above-mentioned community complaints. Therefore, there is a need for an in-depth study on the Quality of Implementation of Identity Card (KTP) of Population and Civil Registration in its service system through Technical Implementation Unit (UPT) of the Department of Population and Civil Registration of the Sub-District.This research was conducted at Technical Implementation Unit (UPT) of Population and Civil Registration Agency of Sub-District with the purpose and intention to know the Quality of Public Service in Population and Civil Registry, especially the service of KTP-electronic through the Technical Implementation Unit (UPT) of the Department of Population and Civil Registration of Sub- , The actors involved in providing the services and knowing the supporting and inhibiting factors affecting the electronic identity card service (KTP). The research method used is Qualitative Method with descriptive research with the technique of digging Information through informant through in-depth interviews either directly or indirectly supported by data contained in the form of Intrument Questionnaire Data Population or Population is the distribution of questionnaires on 50 users of users of Card services Electronic Identity Card (KTP) that conducts electronic subscription card (KTP) application through the Technical Implementation Unit (UPT) of the Department of Population and Civil Registration of Sub-District.From the results of this study it can be seen that the Quality of Implementation of Electronic Identity Card (KTP) services ranging from how the public knows the information electronic identity card (KTP) service mechanism, procedures and mechanisms of making or issuing electronic ID Card (KTP) , All of which are through the Technical Implementation Unit (UPT) of the Department of Population and Civil Registration of the Kecamatan. So hope is the creation of the implementation of demographic services, especially electronic identity card (KTP) is good, fast, precisely what is expected by the community.